A Study on ESG Adoption in Logistics Industry Towards a Carbon-Conscious Reporting Framework for Malaysian SMEs - Vaz, Anthony; Lee Sit Choy, Allan (ExcelingTech, 2025)
As environmental, social, and governance (ESG) practices gain momentum globally, logistics service providers (LSPs) in Malaysia—particularly small and medium-sized enterprises (SMEs)—face growing pressure to adopt ESG frameworks and align with national sustainability mandates. This study investigates the key internal and external factors influencing ESG adoption among logistics SMEs, focusing on readiness for carbon-conscious reporting under the Simplified ESG Disclosure Guide (SEDG). Guided by Stakeholder and Institutional Theory, the study identifies four critical determinants: ESG knowledge and awareness, change readiness, resource availability, and stakeholder engagement. A structured survey of 156 logistics professionals, combined with pilot testing and exploratory factor analysis, confirmed the reliability and validity of the constructs. Regression analysis revealed that all four factors significantly influence ESG adoption, with resource availability being the most dominant predictor. Findings show that knowledge gaps, resistance to change, limited financial resources, and weak stakeholder collaboration hinder effective ESG integration, especially regarding Scope 1–3 emissions reporting. To address these barriers, a five-year roadmap is proposed to help SMEs implement phased ESG strategies, build internal capabilities, and comply with upcoming regulatory requirements, including a potential carbon tax by 2027. This research offers a practical framework for enhancing ESG maturity among logistics SMEs and provides actionable recommendations for policymakers, industry associations, and corporate stakeholders to support sustainable transformation in the Malaysian logistics sector.